IDENTIFICATION OF INDIVIDUALS WITH ACUTE MENTAL DISORDERS IN THE CONTEXT OF PATIENT SAFETY - Andreia Novais Dias Blanco; Renata Flavia Abreu da Silva (Universidade Federal do Paraná, 2019)
Objective: To analyze the identification process for patients in the acute phase of mental disorders in health institutions. Method: Exploratory, qualitative study with data collection conducted between September and December 2018. A digitized questionnaire, whose link was made available through the WhatsApp group of professionals attached to the Brazilian Society for the Quality of Care and Patient Safety, was used. Results: Of the 17 study participants, 64.7% worked in Patient Safety Centers, and all of them were specialists (58.8% in the patient safety area). Of the respondents, 90% do not count on a specific protocol for the identification of these patients in their institutions. The categories created for the strategies were "Adequacy of the Ministry of Health Protocol" and "Protocol of the Ministry of Health", and for the barriers, categories "Inherent Patient Factors" and "Inherent Professional Factors" were created. Conclusion: Important strategies were identified to improve the identification of this clientele.